Galleria mellonella as a Novelty in vivo Model of Host-Pathogen Interaction for Malassezia furfur CBS 1878 and Malassezia pachydermatis CBS 1879 - Torres, Maritza; Pinzón, Elkin Nicolás; Rey, Flor Maria; Martinez, Heydys; Parra Giraldo, Claudia Marcela; Celis Ramírez, Adriana Marcela (Frontiers in Cellular and Infection Microbiology, 2020)
Malassezia furfur and Malassezia pachydermatis are lipophilic and lipid dependent yeasts, associated with the skin microbiota in humans and domestic animals, respectively. Although they are commensals, under specific conditions they become pathogens, causing skin conditions, such as pityriasis versicolor, dandruff/seborrheic dermatitis, folliculitis in humans, and dermatitis and otitis in dogs. Additionally, these species are associated with fungemia in immunocompromised patients and low-weight neonates in intensive care units with intravenous catheters or with parenteral nutrition and that are under-treatment of broad-spectrum antibiotics. The host-pathogen interaction mechanism in these yeasts is still unclear; for this reason, it is necessary to implement suitable new host systems, such as Galleria mellonella. This infection model has been widely used to assess virulence, host-pathogen interaction, and antimicrobial activity in bacteria and fungi. Some advantages of the G. mellonella model are: (1) the immune response has phagocytic cells and antimicrobial peptides that are similar to those in the innate immune response of human beings; (2) no ethical implications; (3) low cost; and (4) easy to handle and inoculate. This study aims to establish G. mellonella as an in vivo infection model for M. furfur and M. pachydermatis. To achieve this objective, first, G. mellonella larvae were first inoculated with different inoculum concentrations of these two Malassezia species, 1.5 × 106 CFU/mL, 1.5 × 107 CFU/mL, 1.5 × 108 CFU/mL, and 11.5 × 109 CFU/mL, and incubated at 33 and 37°C. Then, for 15 days, the mortality and melanization were evaluated daily. Finally, the characterization of hemocytes and fungal burden assessment were as carried out. It was found that at 33 and 37°C both M. furfur and M. pachydermatis successfully established a systemic infection in G. mellonella. M. pachydermatis proved to be slightly more virulent than M. furfur at a temperature of 37°C. The results suggest that larvae mortality and melanization is dependent on the specie of Malassezia, the inoculum concentration and the temperature. According to the findings, G. mellonella can be used as an in vivo model of infection to conduct easy and reliable approaches to boost our knowledge of the Malassezia genus.